2017
DOI: 10.1155/2017/5653643
|View full text |Cite
|
Sign up to set email alerts
|

Erzhi Pill® Repairs Experimental Liver Injury via TSC/mTOR Signaling Pathway Inhibiting Excessive Apoptosis

Abstract: The present study aimed to investigate the mechanism of hepatoprotective effect of Erzhi Pill (EZP) on the liver injury via observing TSC/mTOR signaling pathway activation. The experimental liver injury was induced by 2-acetylaminofluorene (2-AAF) treatment combined with partial hepatectomy (PH). EZP treated 2-AAF/PH-induced liver injury by the therapeutic and prophylactic administration. After the administration of EZP, the activities of aspartic transaminase (AST), alanine aminotransferase (ALT), alkaline ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 79 publications
(76 reference statements)
1
10
0
Order By: Relevance
“…The characteristics of liver injury recurred in the rats with 2-AAF-induced liver injury without treatment, which included decreased concentration of albumin, and elevated AST and ALT, and typical pathological changes. The changes in the Model group were consistent with those in our previous studies ( Zhou et al, 2017 ). We showed that 2-AAF/PH-induced hepatic injury was successfully prepared in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The characteristics of liver injury recurred in the rats with 2-AAF-induced liver injury without treatment, which included decreased concentration of albumin, and elevated AST and ALT, and typical pathological changes. The changes in the Model group were consistent with those in our previous studies ( Zhou et al, 2017 ). We showed that 2-AAF/PH-induced hepatic injury was successfully prepared in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is unclear whether EZP inhibits the PI3K/AKT/Raptor/Rictor signaling pathway to treat liver diseases. In our previous study, we had demonstrated that EZP relieved liver injury induced by 2-acetylaminofluorene/partial hepatectomy (2-AAF/PH), and decreased aminotransferase levels to protect liver tissues by deactivating the TSC/mTOR signaling pathway ( Zhou et al, 2017 ). Nevertheless, as the upstream signal proteins of the TSC/mTOR signaling pathway, the change in the PI3K/AKT signaling pathway and cell cycle were not observed.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis, also known as programmed cell death, is a critical mechanism for maintaining cell stability; however, too much can damage the body [25]. Usually, apoptosis, an early event in kidney I/R injury, interacts with the subsequent inflammation and kidney injury [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the excessive apoptosis has adverse effects on the body. According to reports, apoptosis induces damage to a variety of tissues, including those of the kidney [ 48 , 49 ]. In the present study, TUNEL results showed that apoptosis was involved in the process of kidney injury induced by acute stress.…”
Section: Discussionmentioning
confidence: 99%